Pengaruh kepuasan kerja dan beban kerja terhadap kinerja karyawan pada PT Inkabiz Indonesia - Octavianti, Santi; Hamni, Rahmah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Job satisfaction as a favorable or unfavorable situational condition and how employees view their work. The purpose of this study was to determine the effect of job satisfaction and workload on employee performance at PT Inkabiz Indonesia partially, simultaneously. The method used in conducting this research is quantitative. The results of this study are job satisfaction has a positive and significant effect on employee performance. Hypothesis test obtained value of t count > t table or (5,977 > 1,996). This is also reinforced by the value of value < Sig. 0.05 or (0.000 < 0.05). Thus, Ho1 is rejected and Ha1 is accepted. Workload has a positive and significant effect on employee performance. Hypothesis test obtained value of t arithmetic > t table or (15.399 > 1.996). This is also reinforced by the value of value < Sig. 0.05 or (0.000 < 0.05). Thus, Ho2 is rejected and Ha2 is accepted. Job satisfaction and workload have a positive and significant effect simultaneously on employee performance. The value of the Hypothesis Test is obtained by the calculated F value > F table or (117.574 > 3.13). Thus, Ho3 is rejected and Ha3 is accepted.